At the Back of the North Wind - Lewis, Elizabeth; MacDonald, George, 1824-1905; Kirk, Maria Louise, 1860-1938 (Salt Lake City, UT : Project Gutenberg, 2006)
"At the Back of the North Wind" by George MacDonald is a children's fantasy novel serialized beginning in 1868 and published in book form in 1871. The story follows Diamond, a sweet young boy who befriends the mysterious North Wind, a goddess-like being. Together they embark on nighttime adventures through the sky, where Diamond gradually discovers her true nature. The tale explores deep theological questions while telling the story of a child who brings joy and peace wherever he goes, even as he seems not entirely of this world. (This is an automatically generated summary.)
This is a simplified adaptation of eBook #225.
Wikipedia page about this book: https://en.wikipedia.org/wiki/At_the_Back_of_the_North_Wind
Release date is 2006-06-17
E-text prepared by Joseph R. Hauser, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Fairy tales